Jigsaw Cooperative Learning Model for Improving Large-Ball Game Skills and Empathy among Elementary School Students - Prasandi, Aldiyas; Gumilang, Eva Sri (Sportify Journal, 2025)
Elementary physical education should support students' psychomotor development while also fostering social attitudes through active and collaborative learning experiences. However, large-ball game instruction is often still dominated by teacher-centered practices, limiting students' opportunities to practice fundamental movement skills, interact meaningfully with peers, and develop empathy. This study examined the effect of the Jigsaw cooperative learning model on elementary students' large-ball game skills and empathy. A quantitative experimental method with a one-group pretest-posttest design was employed. The participants were 20 fifth-grade students at SD Negeri 027 Cicadas, Bandung, selected through purposive sampling from a population of 28 students. Data were collected using a futsal basic skills test covering dribbling, passing, ball control, and shooting, and a Likert-scale empathy questionnaire. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and effect size estimation. The findings showed that students' large-ball game skills and empathy improved significantly after participating in Jigsaw-based physical education learning. The statistical results indicated significant pretest-posttest differences in both variables, supported by strong practical effects. These findings suggest that the Jigsaw cooperative learning model can create an active, collaborative, and socially meaningful learning environment that enhances psychomotor performance while strengthening empathy among elementary school students.